Helpful Approaches for Older Adults Living in a Retirement Community to Move Forward After the Death of a Significant Other. Issue 3 (2nd July 2020) - Sopcheck, Janet
Abstract: The loss of a significant other often creates emotional distress for family members that can hamper the ability to meet everyday challenges and pursue wellness. The aim of this qualitative study was to understand the challenge of losing a significant other for older adult family members and the approaches identified as most helpful to promote their own well-being after this person dies. Story inquiry method guided the interview process with 15 older adult bereaved family members residing in a continuing care retirement community. Theory-guided content analysis was used for data analysis. Two themes described the challenges: uneasiness that permeates everyday living and precious memories and patterns of disconnect that breed discontent. Appreciating the rhythmic flow of everyday connecting and separating and embracing reality as situated in one's lifelong journey are the themes that encompass the helpful approaches used by participants. This study provided insights about the benefits of living in this community such as social networking and a possible drawback such as the frequency of death among residents. Future research should continue to investigate social service resources that older adults find most helpful after a significant other dies and the use of reminiscence groups as a form of bereavement support.